2018
DOI: 10.1101/503193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anticorrelated inter-network electrophysiological activity varies dynamically with attentional performance and behavioral states

Abstract: The default mode network (DMN) is thought to exhibit infraslow anticorrelated activity with dorsal attention (DAN) and salience (SN) networks across various behavioral states. To investigate the dynamics of activity across these networks on a finer timescale, we used human intracranial electroencephalography with simultaneous recordings within core nodes of the three networks.During attentional task performance, the three sites showed dissociable profiles of high-frequency broadband activity. Anticorrelated in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 103 publications
1
7
0
Order By: Relevance
“…Furthermore, a recent intracranial electroencephalography study in humans revealed that default and dorsal attention network activity was more anticorrelated during periods of better attention task performance, and that dorsal attention activations preceded (and potentially caused) default mode deactivations (Kucyi et al, 2018). Complementing these findings, our results demonstrate for the first time that the same functional networks that predict individual differences in attention in novel individuals also predict attentional states specific to task blocks, fMRI sessions, and states of consciousness induced by anesthesia.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, a recent intracranial electroencephalography study in humans revealed that default and dorsal attention network activity was more anticorrelated during periods of better attention task performance, and that dorsal attention activations preceded (and potentially caused) default mode deactivations (Kucyi et al, 2018). Complementing these findings, our results demonstrate for the first time that the same functional networks that predict individual differences in attention in novel individuals also predict attentional states specific to task blocks, fMRI sessions, and states of consciousness induced by anesthesia.…”
Section: Discussionsupporting
confidence: 79%
“…Functional MRI (fMRI) studies in humans have linked these moment-to-moment attention fluctuations to ongoing activity in large-scale brain networks including the default mode, dorsal attention, and salience networks (Christoff et al, 2009;Fortenbaugh et al, 2018;Kucyi et al, 2016a;Leber, 2010;Rosenberg et al, 2015;Weissman et al, 2006). A growing body of work has also related changes in fMRI and intracranial electroencephalography functional connectivity to changes in attentional and cognitive states (Gonzalez-Castillo et al, 2015;Kucyi et al, 2016bKucyi et al, , 2018Shappell et al, 2019;Shine et al, 2016a;Turnbull et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During conditions that engage external attention, the reduction of functional activity in the DMN (Greicius et al, 2003, Shulman et al 1997, is concomitant with an increase of activity in the DAN and ECN (Seeley et al 2007;Dosenbach et al 2007;Fox et al, 2005;Sridharan et al 2008). The anticorrelation between these is related to individual differences in performance variability (Kelly 2008), and directly supports sustained attention (Kucyi et al, 2020). More broadly, it has been suggested to facilitate ongoing switches between internally-and externally biased modes of attention (Honey et al, 2017;Buckner et al, 2013) that contribute to consciousness (Carhart-Harris and Friston 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The extant iEEG studies have provided some initial electrophysiological findings for relationships among distinct brain regions that are typically thought as key nodes of brain networks, though the results seemed to be discrepant. For example, the PCC, one key region of DMN, has been reported to be correlated with the angular gyrus (Foster, Rangarajan, Shirer, & Parvizi, 2015) and mPFC (A. Kucyi et al, 2018) through high frequency band power fluctuations in resting state, while another study failed to find such high-frequency band DMN correlates but found stronger theta (4-8 Hz) band-limited power correspondence in the DMN and FPN, and stronger alpha (8-12 Hz) correspondence in the SMN and DAN (Hacker, Snyder, Pahwa, Corbetta, & Leuthardt, 2017).…”
Section: Introductionmentioning
confidence: 99%